2021
DOI: 10.3390/ijerph18041606
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Burnout Syndrome for Public Schoolteachers in the Brazilian Context: A Systematic Review

Abstract: The aim of this systematic review was to examine the prevalence of burnout-related symptoms in Brazilian schoolteachers who work in public schools. The literature search was conducted using the following databases: PubMed-MEDLINE, Scopus, and Web of Science. Peer-reviewed studies published in English, Spanish, or Portuguese were considered for inclusion. A total of 2106 records were identified through database searching and 7 additional studies were identified through other sources. Based on the inclusion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
0
7
0
3
Order By: Relevance
“…Considering other studies carried out during the COVID-19 pandemic and associated problems faced by teachers directly contributing to professional exhaustion [ 34 , 39 ], more severe scores were expected in our study, since the percentage of teachers with high and moderate levels of burnout was low. Previous studies carried out studying burnout among Brazilian university professors [ 15 , 20 ], as well as among teachers from other levels of education, and according to a systematic review carried out by Montoya et al [ 29 ], also demonstrate this trend.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Considering other studies carried out during the COVID-19 pandemic and associated problems faced by teachers directly contributing to professional exhaustion [ 34 , 39 ], more severe scores were expected in our study, since the percentage of teachers with high and moderate levels of burnout was low. Previous studies carried out studying burnout among Brazilian university professors [ 15 , 20 ], as well as among teachers from other levels of education, and according to a systematic review carried out by Montoya et al [ 29 ], also demonstrate this trend.…”
Section: Discussionmentioning
confidence: 75%
“…Exhaustion, the dimension most affected in the sample of this study, represents fatigue and extreme tiredness, mentioned by some authors as the core of the burnout syndrome construct [ 27 , 28 ]. Other studies point out that even in samples with no burnout, the level of teacher exhaustion is high [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that long-term absence from work occurred more often in older teachers [ 13 ]. A systematic review reports that Brazilian public school teachers have high levels of emotional exhaustion in combination with a prevalence of burnout—nonetheless, they are persistently motivated and idealist [ 48 ], which may help them continue working, despite being sick. Voice symptoms are better recognized by others because they are physical and restrict or limit communication in the classroom, unlike psychological symptoms, which are often neglected or not legitimated.…”
Section: Discussionmentioning
confidence: 99%
“…Once the information has been extracted, brainstorming session was then held to discuss and resolve the items (indicators or predictors) that generated disagreement. Any discrepancies during the data extraction and analysis process were resolved by consensus among the members of the research team (Montoya et al, 2021).…”
Section: Methodsmentioning
confidence: 99%